Recurrence Prediction by Multi-Omics in the Patient with Colorectal Peritoneal Metastases After Cytoreductive Surgery: A Prospective Biomarker Study - Chen C; Gong Z; Zhang Z; Gu H; Zhu A; Peng D; Li B; Wang J; Hu Y; Wang D; Sun L (Cancer Management and Research)
Chao Chen,1– 3,* Zhiyuan Gong,1– 3,* Zhiwei Zhang,1– 3 Haochen Gu,1– 3 Akao Zhu,1– 3 Di Peng,4 Bing Li,4 Jian Wang,1 Yeting Hu,1 Da Wang,1 Lifeng Sun1 1Department of Colorectal Surgery and Oncology, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang Province, People’s Republic of China; 2Key Laboratory of Cancer Prevention and Intervention, China National Ministry of Education, Beijing, Zhejiang Province, People’s Republic of China; 3Zhejiang University Cancer Center, Hangzhou, Zhejiang Province, People’s Republic of China; 4Guangzhou Ranshi Medical Laboratory Co., Ltd, Guangzhou, Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Da Wang, Department of Colorectal Surgery and Oncology, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang Province, People’s Republic of China, Tel +86-571-87784720, Email wangda0618@zju.edu.cn Lifeng Sun, The Second Affiliated Hospital, Zhejiang University School of Medicine, 88 Jiefang Road, Hangzhou, Zhejiang, 310009, People’s Republic of China, Tel +86-571-87783586, Email sunlifeng@zju.edu.cnBackground: Colorectal cancer with peritoneal metastases (CRCPM) exhibits high recurrence post-cytoreductive surgery (CRS). This study evaluated tumor tissue biomarkers and combined circulating tumor DNA (ctDNA) and methylation analysis via ultra-deep next-generation sequencing (NGS) for recurrence prediction.Methods: CRCPM patients undergoing surgery were enrolled (n=21). Blood samples was collected at preoperative and postoperative, and tumor and adjacent tissues were collected. NGS assessed ctDNA and methylation in blood samples, while tumor mutations and methylation were analyzed in tumor. Recurrence was determined via imaging. Outcomes included progression-free survival (PFS) and overall survival (OS).Results: Of 17 patients with paired pre-/postoperative ctDNA testing, preoperative ctDNA levels were higher in those with extraperitoneal metastases versus peritoneal-only disease (0.1064 vs 0.0037). Postoperative ctDNA positivity correlated with 100% peritoneal recurrence. ctDNA-positive subgroups showed shorter PFS (HR=2.5; 95% CI:1.6– 6.6). Patients persistently ctDNA-negative pre-/postoperatively had improved PFS versus those with positivity (HR=5.07; 95% CI:0.53– 48.38). ctDNA methylation positivity was observed in all extraperitoneal metastasis cases and 70% of peritoneal-only cases. Baseline methylation positivity predicted worse OS overall and in peritoneal-only subgroups. Postoperative dual negativity for ctDNA and methylation correlated with better OS. Tumor mutations in EPHB1 (P = 0.012), ARFRP1 (P = 0.048), and ATR (P = 0.048) were significantly associated with PFS.Conclusion: Dynamic ctDNA and methylation monitoring, and tumor mutation profiling, may serve as sensitive biomarkers for early recurrence detection in CRCPM underwent CRS. These tools could enhance recurrence prediction and guide clinical management.Keywords: circulating tumor DNA, colorectal cancer, peritoneal metastasis, ctDNA methylation, timing of recurrence, mutations